(3QSGdI GdMbGFb hGdEfPGQ hGdJCOjH dLejY GdNdGFbs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce HGdMb hebje GdMLI HhdjI GdbGFe Ydi LejY GdNdb s
(3BNQgG (B:s
(3Gddge aHc GdeSJZGK hEdjc GdeTcGO hai jOc GdeeGJ hGdeMjG hEdjc Hhdjc GdeaRY GdMeO dehdGfG GdMGce hMOg hGdTcQ ddEeGe GdgGOi YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B57s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds